Les misérables / Victor Hugo. - Hugo, Victor, 1802-1885. (Tufts University. Tisch Library., 2016)
1 online resource (8 volumes).; Volume 5 of 8.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.